ETHICAL IMPLICATIONS OF AI IN LANGUAGE EDUCATION - Mavlonova Sevinch Murodjon qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis explores the ethical implications of integrating artificial intelligence (AI) into language education. It examines issues such as data privacy, algorithmic bias, teacher-student dynamics, and dependency on technology. The study emphasizes the need for balanced and ethical implementation of AI tools to enhance learning while protecting human values.